Unexamined faiths and the public place of religion: emerging insights from the law - Iain T. Benson (Acta Theologica)
The article examines certain key terms, such as “beliefs” and “faith” and how these are understood in relation to the public sphere. It examines some writings of recent popularist authors such as Richard Dawkins and Christopher Hitchens, and is critical of the authors’ claims that they do not have faith or beliefs. Drawing on legal decisions in Canada and South Africa the article suggests that this sort of terminological looseness has legal and political implications when it comes to whether or not beliefs of all sorts (religious and non-religious) are treated fairly in the public sphere. Arguing for a more diverse public sphere, the article cautions that law should give greater attention to principles of modus vivendi rather than “convergence” in which the attempt is to eradicate legally allowable positions from the public sphere and place those who hold them, and their communities, at a disadvantage. The law must not, by inflating its own role, put added pressures on the liberty that accommodation and subsidiarity require.